Pengaruh Self-Congruence dan Shopping Value Terhadap Compulsive Buying Produk Lifestyle - Andriana, Erica; Cyrious, Cyrious; Yonda Asepta, Uki (Masyarakat Ekonomi Syariah Bogor, 2024)
This is a new author's manual and a template for Jurnal Dirosah Islamiyah. Published every May and November since 2019. Articles must start with Article Title followed by Author Name and Affiliate Address and abstract. This part of the abstract must be typed in 150-250 word counts. Especially for the abstract, use the Cambria font, measuring 10 pt. Single space per line in this article. If the article is written in Indonesian, the abstract should be typed in English and Indonesian. Meanwhile, if the article is written in English, the abstract must be typed in English only. The abstract is typed as concisely as possible and consists of: research objectives, methods, results and discussion and brief conclusions. 250 words maximum. Abstract should only be typed in one paragraph and in one column format.